2010
DOI: 10.3109/08958370903295204
|View full text |Cite
|
Sign up to set email alerts
|

Inhalability of micron particles through the nose and mouth

Abstract: Aspiration efficiencies from nose and mouth inhalations are investigated at low and high inhalation rates by using the commercial Computational Fluid Dynamics (CFD) software CFX 11. A realistic human head with detailed facial features was constructed. Facial features were matched to represent the 50th percentile of a human male, aged between 20 and 65 years old, based on anthropometric data. The constant freestream velocity was 0.2 ms(-1), normal to the face, and inhalation rates through the mouth and nose wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Some researchers reported velocity profile as the basis for conducting mesh refinement, (6,7,16) others reported airflow, deposition fractions, pressure drop, wall shear stress, or combination of CFD variables. (2,3,13,17,20) A number of other investigators did not specify the variables computed to determine grid independent control volume. (1,(8)(9)(10)(11)14,15) (3) There are no standardized nasal characteristics that investigators conform to when reconstructing nasal geometry for CFD studies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some researchers reported velocity profile as the basis for conducting mesh refinement, (6,7,16) others reported airflow, deposition fractions, pressure drop, wall shear stress, or combination of CFD variables. (2,3,13,17,20) A number of other investigators did not specify the variables computed to determine grid independent control volume. (1,(8)(9)(10)(11)14,15) (3) There are no standardized nasal characteristics that investigators conform to when reconstructing nasal geometry for CFD studies.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of consistency in the literature on the number and type of grid elements required to provide numerically accurate CFD solutions for studies involving sinonasal insilico analysis of airflow and particulate matter, (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) even though most investigators performed airflow simulation using the finite volume method software package, FluentÔ (ANSYS, Inc., Canonsburg, PA). Among studies where mesh density analyses were reported, some authors failed to report details regarding how mesh refinement was done to achieve grid-independent numerical solutions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of particle deposition in confined flows of irregular geometries such as the human upper airways have also been performed. These include the oral cavity (Tian, Longest, Su, Walenga, & Hindle, 2011;Yousefi, Inthavong, & Tu, 2015) , the nasal cavity (Ge, Inthavong, & Tu, 2012;Se, Inthavong, & Tu, 2010;Wang et al, 2009;Zamankhan et al, 2006), and the lower respiratory tract (Xi, Longest, & Martonen, 2008;Zhang & Kleinstreuer, 2003;Zhang & Kleinstreuer, 2011;Piglione, Fontana, & Vanni, 2012).…”
mentioning
confidence: 99%